ANALISIS BIAYA SATUAN PADA PASIEN RAWAT INAP DIABETES MELITUS TIPE 2 DENGAN METODE ACTIVITY BASED COSTING DI RS PKU MUHAMMADIYAH BANTUL - Winny Ardhitia Garini (MMR UMY, 2016)
Background: Since January 1, 2014 a change in the health payment system that initially fee for service system into a system of prospective Indonesian case based Group’s (INA-CBG’s). This caused the hospital management evaluation costs related to patient care. One of the diseases that have chronicity and require long-term care is Diabetes Mellitus, which according to WHO these diseases will increase in 2030 of 21.3 million. In PKU Muhammadiyah Hospital in Bantul ever do analysis on cases of typhoid fever and obtained the difference of greater costs incurred by hospitals compare tariff INA-CBGs, and for cases of Diabetes Mellitus has never been done analiis calculation, so this research aims to calculate the unit cost method of Activity Based Costing Diabetes mellitus patient care and then compare it with the real cost and tariff INA CBG’s. Methods: This study was descriptive quantitative case study design at PKU Muhammadiyah Hospital in Bantul, selected cases were patients who had a diagnosis of ICD X: E-4-10-I (Diseases and Disorders of Nutrition Diabetes / Mild Metabolic). Results and Discussion: The results of calculation of the unit cost of type 2 diabetes mellitus patients with ABC method is Rp 1.908.985,08, consisting of direct costs in the amount of Rp 1.711.589,00 and overhead expenses amounting to Rp 197. 396. Conclusion: Based on the calculation of unit cost for patients with Type 2 Diabetes Mellitus is Rp 1.908.985,08, there is a difference of Rp 107.730,92 with the real cost is in PKU Muhammadiyah Hospital in Bantul and the difference amounting to Rp 33.914,92 with INA tariff CBG’s.